Valorization of Anaerobic Liquid Digestates Through Membrane Processing and Struvite Recovery—The Case of Dairy Effluents - Anthoula C. Karanasiou; Charikleia K. Tsaridou; Dimitrios C. Sioutopoulos; Christos Tzioumaklis; Nikolaos Patsikas; Sotiris I. Patsios; Konstantinos V. Plakas; Anastasios J. Karabelas (Membranes)
An integrated process scheme is developed for valorizing filtered liquid digestates (FLD) from an industrial anaerobic digestion (AD) plant treating dairy-processing effluents with relatively low nutrient concentrations. The process scheme involves FLD treatment by nanofiltration (NF) membranes, followed by struvite recovery from the NF-retentate. An NF pilot unit (designed for this purpose) is combined with a state-of-the-art NF/RO process simulator. Validation of simulator results with pilot data enables reliable predictions required for scaling up NF systems. The NF permeate meets the standards for restricted irrigation and/or reuse. Considering the significant nutrient concentrations in the NF retentate (i.e., ~500 mg/L NH4-N, ~230 mg/L PO4-P), struvite recovery/precipitation is investigated, including determination of near-optimal processing conditions. Maximum removal of nutrients, through production of struvite-rich precipitate, is obtained at a molar ratio of NH4:Mg:PO4 = 1:1.5:1.5 and pH = 10 in the treated stream, attained through the addition of Κ2HPO4, ΜgCl2·6H2O, and NaOH. Furthermore, almost complete struvite precipitation is achieved within ~30 min, whereas precipitate/solid drying at modest/ambient temperature is appropriate to avoid struvite degradation. Under the aforementioned conditions, a significant amount of dry precipitate is obtained, i.e., ~12 g dry mass per L of treated retentate, including crystalline struvite. The approach taken and the obtained positive results provide a firm basis for further development of this integrated process scheme towards sustainable large-scale applications.